Synthesis and characterization of vinyl-functionalized magnetic nanofibers for protein imprinting. Issue 1 (12th November 2014) - Li, Yanxia; Bin, Qiu; Lin, Zhenyu; Chen, Yiting; Yang, Huanghao; Cai, Zongwei; Chen, Guonan
Abstract : One kind of surface protein imprinting method was developed by a more convenient, simpler and cheaper approach based on vinyl-functionalized magnetic nanofibers (NFs). Abstract : One kind of surface protein imprinting method was developed by a more convenient, simpler and cheaper approach based on vinyl-functionalized magnetic nanofibers (NFs).